Foreword - Randall, William (Narrative Works, 2019)
It is difficult to do justice in a page or so to a book whose implications are as far-reaching as those of this one. As someone who has devoted the whole of his scholarly career to the study of stories—of how they are integral to virtually every aspect of our lives (our identities, relationships, emotions, and beliefs)—I heartily commend Listening to Stories of Courage and Moral Choice as a testament to the power of narrative to effect positive, transformative change in the world.